Comparison of two doses of intravenous temsirolimus in patients with relapsed/refractory mantle cell lymphoma. Issue 3 (4th March 2018) - Jurczak, Wojciech; Ramanathan, Sundra; Giri, Pratyush; Romano, Alessandra; Mocikova, Heidi; Clancy, Jill; Lechuga, Mariajose; Casey, Michelle; Boni, Joseph; Giza, Agnieszka; Hess, Georg
Abstract: Temsirolimus 175 mg once-weekly for 3 weeks, followed by 75 mg once-weekly intravenously dosed (175/75 mg) is approved in the European Union for treatment of relapsed/refractory mantle cell lymphoma (MCL). A phase IV study explored whether similar efficacy, but improved safety could be achieved with 75 mg without 175 mg loading doses (ClinicaTrials.gov: NCT01180049). Patients with relapsed/refractory MCL were randomized to once-weekly temsirolimus 175/75 mg ( n  = 47) or 75 mg ( n  = 42). Treatment continued until objective disease progression. Primary endpoint: progression-free survival (PFS). Secondary endpoints included overall survival (OS) and adverse events (AEs). Median PFS was 4.3 versus 4.5 months (hazard ratio [HR] 0.731; 80% confidence interval [CI], 0.520–1.027), and median OS 18.7 versus 11.0 months (HR 0.681; 80% CI, 0.472–0.982) with 175/75 mg versus 75 mg. There were fewer patients with serious AEs, dose reduction, or death with 175/75 mg (57.4%, 48.9%, and 48.9%) versus 75 mg (73.8%, 64.3%, and 65.1%). Temsirolimus 175/75 mg remains the preferred dosing regimen for relapsed/refractory MCL.